Neutral and charged excitons in a CdTe-based quantum well: Низкоразмерные и сверхпроводящие системы - Gaj, J.A.; Kossacki, P.; Unicode``>&#322ochocka, P. P<font face=`Lucida Sans; Maślana, W.; Cibert, J.; Tatarenko, S.; Radzewicz, C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We present a summary of our spectroscopic studies of the oscillator strength of transitions related to the formation of neutral and positively charged excitons in modulation p-dopedCdTe-based quantum wells. The hole concentration was controlled in the range from 1010 cm-2 to 1011 cm-2 . Continuous-wave and time-resolved femtosecond pump–probe absorption measurementswere performed. They allowed us to study the interacting system of excitons, trions, and free holes. Characteristic times of the system were determined, such as the trion formation time. A new explanation of so-called oscillator strength «stealing» has been proposed, in terms of spin-dependent screening. Experimental evidence is presented for optical creation of transient spin polarizationin the quantum well.